Rational Emotive Behavior Therapy dalam Mengubah Perilaku Fanatik Korean Pop pada Santri - Qurrotul Faizah; M.Syakur (Konseling At-Tawazun, 2023)
In Indonesia, people are starting to like Korean Pop, starting with Korean drama series. Korean Pop really affects all people from all sectors. Starting from the urban community to the village, from children to adults including students as people who study at Islamic boar[1]ding schools. There are things that don’t work out in harmony when a student likes Korean Pop. There are six principles of the santri lifestyle in Islamic boarding schools. One of them is exemplary. There are lifestyle principles that start to shift if the students are fond of Kore[1]an Pop and even fanatical. Mainly on the principle of exemplary. Santri choose idols without filter and exaggeration. The purpose of this study is to describe Rational Emotive Behavior Therapy in Changing the Behavior of Korean Pop Fanatics in Santri. The research method used is Action Research. Action research is a method used to study a problem, find a solu[1]tion to the problem and make improvements in real action on a particular class. The results of this study are able to make the counselee reduce the habit of fanaticism. Such as daydrea[1]ming, hysterics, screaming, wasting money and neglecting duties. So that the counselee can live healthily and effectively.